Peramalan Jumlah Produksi Minyak Kelapa Sawit Menggunakan Metode Holt-Winters Exponential Smoothing (Studi Kasus : PT. Sinar Gunung Sawit Raya) - Handrianto, Michael; Cipta, Hendra (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2023)
PT. Sinar Gunung Sawit Raya (SGSR) is a company operating in the palm oil plantation sector, producing palm oil and palm kernels. The company faces the challenge of palm oil production variability related to seasonal fluctuations, particularly in the number of fresh fruit bunches (FFB) from oil palm plantations and the FFB delivered to the mill. Palm oil production is significantly affected by seasons, with production increasing during certain months, such as the rainy season when oil palm fruits are larger and heavier, resulting in higher oil yields. Conversely, during the dry season, the fruits tend to be smaller and lighter, leading to a decline in palm oil production. This research aims to forecast palm oil production for the following two periods using the Holt-Winters Exponential Smoothing method with both additive and multiplicative models. Forecasts are conducted manually and with the assistance of Microsoft Excel software. The forecast accuracy is assessed using the Mean Absolute Percentage Error. The manual forecasts for the additive and multiplicative models yielded error rates of 2.11% and 11.56%, respectively. While these forecasts provide valuable insights, it should be noted that other factors may also influence palm oil production outcomes. Therefore, these forecasting results can assist the company in formulating policies to enhance palm oil production.